Publishing Services of "Bazm-e-Takhliq-o-Tehqiq Pakistan": Research and Analysis - Sahir, Muhammad Hassnain; Shaheen, Shazia; Kasairvi, Shakil (sourcecoder, 2024)
Before and after the establishment of Pakistan, several literary organizations of historical importance have been fulfilling the responsibility of promoting literature and training the new generation in an auspicious manner. Even now, many literary organizations in Pakistan are playing their active role in the field of Pakistani language and literature. Bazm-e-Takhliq-o-Tehqiq Pakistan is also one of such organizations. Bazm-e-Takhliq-o-Tehqiq Pakistan, based in Islamabad, is a purely literary organization, which was established on March 8, 2013. Mainly the aim of this organization is to give trend to scholarly and literary activities in and around Islamabad, in which the organization has achieved considerable success. The most important achievement of Bazm-e-Takhliq-o-Tehqiq Pakistan is that it has published 22 books (in the categories of poetry, prose, research and criticism) within ten years of its establishment. Among the authors whose books have been published by Bazm-e-Takhliq-o-Tehqiq Pakistan, Prof. Muhammad Saqlain Zaigham, Dr. Shaukat Mehmood Shaukat, Dr. Hassnain Sahir, Dr. Shakeel Kasairvi and Dr. Nisar Ahmed, are important. This paper attempts to provide an introductory overview of the publishing services of this organization.